The Effect of Digital Tax Services on MSME Taxpayer Compliance with Tax Literacy as Moderator - Sri Depi; Mediaty; Akhmad Qusyairi Amiruddin (Universitas Muhammadiyah Makassar, 2026)
The increasing adoption of digital tax services has raised important questions regarding their effectiveness in encouraging taxpayer compliance, particularly among Micro, Small, and Medium Enterprises (MSMEs) whose engagement with the digital fiscal system is influenced by technological factors and tax literacy. This study aims to analyze the effect of digital tax service utilization on MSME taxpayer compliance in Makassar City, with tax literacy as a moderating variable. A quantitative design was employed, with data collected from 89 MSME taxpayers registered at the local Tax Service Office through a structured Likert-scale questionnaire using a purposive sampling technique. Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4 was applied to assess both direct and interaction effects of moderation. The results reveal that the utilization of digital tax services has a significant positive effect on MSME taxpayer compliance (β = 0.438, T = 5.441, p = 0.000), and that tax literacy significantly moderates this relationship (β = 0.421, T = 3.789, p = 0.000), with the model explaining 48.6% of the variance in compliance. These findings extend the Technology Acceptance Model and the Theory of Planned Behavior by demonstrating that tax literacy strengthens the compliance-enhancing impact of digital tax platforms, serving as a critical cognitive enabler for MSME taxpayers. This study contributes theoretically by positioning tax literacy as a moderating construct within the behavioral compliance framework, and practically by recommending an integrated policy strategy that combines digital infrastructure development with tax literacy education programs to maximize compliance outcomes among MSME taxpayers.